The Zoomorphic Arts of Ancient Central Eurasia - Andreeva, Petya (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The volume focuses on the zoomorphic art and design systems of ancient China and Central Asia. It offers a glimpse into convergent and shifting concepts of zoomorphism across political and cultural boundaries, and places special emphasis on nomadic cultural spheres. The papers explore the role of animals in one's creative process and the factors that might have contributed to the formation of a zoomorphic image system across different parts of ancient Central Eurasia. The reprint presents studies that span the disciplinary boundaries of Art History, Archaeology, Socio-Cultural Anthropology, and covers archaeological sites and museum collections from a vast geographical domain, from southern China to Kazakhstan and Siberia.